Rational Feeding of live stock - Harman, John Bright (My University, 1895)
Introduction: The greatest question that imprints the practical stock feeder of today is what must he feed his stock in order that they may make the greatest possible gain at the least possible cost. Kansas annually sends to the markets millions of dollars worth of live stock. The question now arises, is this stock fed and marketed to the best advantage? When so large an amount is involved the saving of a small percent would in the aggregate foot up to an enormous sum.
Citation: Harman, John Bright. Rational Feeding of live stock. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Stock feeder; Kansas; Food; Theses; Manuscripts (documents)